2017
DOI: 10.1177/1010428317710822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor architecture on disease recurrence and cancer-specific mortality of upper tract urothelial carcinoma treated with radical nephroureterectomy

Abstract: Upper tract urinary carcinoma (UTUC) is a relatively uncommon but aggressive disease. Recent publications have assessed the prognostic significance of tumor architecture in UTUC, but there is still controversy regarding the significance and importance of tumor architecture on disease recurrence. We retrospectively reviewed the medical records of 101 patients with clinical UTUC who had undergone surgery. Univariate and multivariate analyses were conducted to identify factors associated with disease recurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…After punctilious reading, 358 studies were excluded; of these, 279 studies were excluded because they did not provide sufficient data, 56 articles were excluded as the same participants were included in other studies, and 23 articles were excluded as there were of low quality. Finally, 17 studies [ 12 , 16 31 ] published from 2014 to 2019, which met all of the inclusion and exclusion criteria, were enrolled in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After punctilious reading, 358 studies were excluded; of these, 279 studies were excluded because they did not provide sufficient data, 56 articles were excluded as the same participants were included in other studies, and 23 articles were excluded as there were of low quality. Finally, 17 studies [ 12 , 16 31 ] published from 2014 to 2019, which met all of the inclusion and exclusion criteria, were enrolled in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that tumor architecture may indicate a more advanced stage and it may be associated with more aggressive oncological behavior in UTUC patients. Fan et al [ 12 ] and Margulis et al [ 38 ] showed that sessile tumor architecture was significantly associated with the risk of disease recurrence and it was proved to be a reliable prognostic factor in patients with UTUC. Remzi et al [ 13 ] provided evidence that sessile tumor architecture was associated with more aggressive behavior and was an independent risk factor for tumor recurrence and CSS after RNU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies have been conducted to identify the significant prognostic factors of UTUC. Some traditional prognostic predictors, such as pathologic characteristics of RNU specimens including tumor stage and grade [39], tumor architecture [20], tumour size [23] and CIS [42] had been found as significant prognostic variables for CSS and RFS in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, there were controversial predictive factors that resulted in poor prognosis for UUT-UC and intravesical recurrence, such as patient-speci c factors (age, sex, diabetes mellitus or history of bladder cancer), tumor-related factors (location, size, T stage or architecture) and environmental factors (smoking, long-term use of aristolochic acid, etc.) [9][10][11][12][13]. It is worth noting that the 2-year recurrence-free survival rate is less than 56% for stage ≥pT1 cancer, and the 5-year speci c survival rate is less than 50% for stage ≥pT2 [14].…”
Section: Introductionmentioning
confidence: 99%